Fichas - Juan Manuel Heredia; Gabriel Entin; Martín Bergel; Ximena Espeche; Anahi Ballent; Flavia Fiorucci; Ricardo Martínez Mazzola; Sebastian Malecki; Ximena Espeche; Laura Prado Acosta (Prismas, 2020)
Libros fichados: